Effect of Ag Addition on the Electrochemical Performance of Cu10Al in Artificial Saliva - R. J. Salgado-Salgado; J. Porcayo-Calderon; O. Sotelo-Mazon; R. A. Rodriguez-Diaz; G. Salinas-Solano; V. M. Salinas-Bravo; L. Martinez-Gomez (Bioinorganic Chemistry and Applications)
In this work we proposed to evaluate the corrosion resistance of four different alloys by electrochemical techniques, a binary alloy Cu10Al, and three ternary alloys Cu10Al-xAg (x = 5, 10, and 15 wt.%) to be used like biomaterials in dental application. Biomaterials proposed were tested in artificial saliva at 37°C for 48 h. In addition, pure metals Cu, Al, Ag, and Ti as reference materials were evaluated. In general the short time tests indicated that the Ag addition increases the corrosion resistance and reduces the extent of localized attack of the binary alloy. Moreover, tests for 48 hours showed that the Ag addition increases the stability of the passive layer, thereby reducing the corrosion rate of the binary alloy. SEM analysis showed that Cu10Al alloy was preferably corroded by grain boundaries, and the Ag addition modified the form of attack of the binary alloy. Cu-rich phases reacted with SCN− anions forming a film of CuSCN, and the Ag-rich phase is prone to react with SCN− anions forming AgSCN. Thus, binary and ternary alloys are susceptible to tarnish in the presence of thiocyanate ions.